In vitro pre-selection criteria for probiotic Lactobacillus acidophilus TS1 isolated from fermented milk product, Dahi - Maqsood, S.; Hassan, F.; Masud, T.; Sammi, S.; Naqvi, S. M. S. (Malaysian Journal of Microbiology, 2013)
Aims: The aim of this research was to evaluate some probiotic traits of Lactobacillus acidophilus TS1 strain previously isolated from dahi. Methodology and results: For this purpose, tested strain was evaluated for their resistance to low pH, tolerance to bile and in vitro antibiotics susceptibility. It was observed that the strain TS1 remained viable at pH 3.0 to 6 and bile concentration of 0.1 to 0.3%. Conclusion, significance and impact of study: L. acidophilus TS1 was found resistant to nalidixic acid, ciprofloxacine, gentamycin and vancomycin. The results highlighted the probiotic potential of L. acidophilus TS1 which deserves further investigation in vitro studies to elucidate its health benefits.